2022
DOI: 10.1055/s-0042-1755194
|View full text |Cite
|
Sign up to set email alerts
|

Reducing care time after implementing protocols for acute ischemic stroke: a systematic review

Abstract: Background The treatment of acute ischemic stroke with cerebral reperfusion therapy requires rapid care and recognition of symptoms. Objective To analyze the effectiveness of implementing protocols for acute ischemic stroke in reducing care time. Methods Systematic review, which was performed with primary studies in Portuguese, English, and Spanish published between 2011 and 2020. Inclusion criteria: study population should comprise people with acute ischemic stroke and studies should prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…There was no significant reduction regarding the length of stay, corroborating results from a literature review [12], which show that the length of stay is linked to the patient's health status and/or their pre-existing conditions, as well as complications that may occur during treatment.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…There was no significant reduction regarding the length of stay, corroborating results from a literature review [12], which show that the length of stay is linked to the patient's health status and/or their pre-existing conditions, as well as complications that may occur during treatment.…”
Section: Resultssupporting
confidence: 82%
“…A literature review identified the importance and relevance of implementing protocols in stroke care and their effectiveness in reducing the time elapsed between the onset of symptoms and the start of treatment [12], as well as increasing the performance of reperfusion therapies and improving prognosis after discharge [13].…”
Section: Introductionmentioning
confidence: 99%
“…A decade later, Rocha et al demonstrated that Brazilian SU care, while not impacting LOS, correlated with reduced in-hospital and 30-day mortality rates compared to GW care [21]. A recent systematic review analyzed the effectiveness of implementing AIS protocols in reducing care time, encompassing primary studies published between 2011 and 2020 [22]. Notably, among the included studies, none involved Brazilian patients.…”
Section: Introductionmentioning
confidence: 99%
“…Esse tempo diminuiu ainda mais após tal período, indicando os efeitos da reorganização dos fluxos dentro da instituição, tornando mais rápido o início do tratamento e atingindo as metas propostas. Isto mostra que, de fato, há uma maior necessidade de o município investir em ações para a redução do tempo do APH com a intenção de aumentar a quantidade de pessoas elegíveis para o recebimento de tratamento trombolítico.Quanto ao tempo de internação, não se identificou redução significativa, corroborando com resultados de uma revisão da literatura(LEITE et al, 2022) que mostrou que em apenas dois de 30 artigos analisados houve diminuição em tal tempo. Ou seja, é possível refletir que talvez que o tempo de internação esteja atrelado ao estado de saúde da vítima e/ou suas condições pré-existentes, bem como às complicações que podem ocorrer durante o tratamento.Quanto aos desfechos dos casos de AVC isquêmico do estudo submetidos à trombólise, identificou-se que a proporção de ocorrências desfavoráveis aumentou em consonância com o aumento da gravidade dos casos, assim como no estudo NINDS (1995), em que as vítimas com escore NIHSS >20 tiveram 17% de chance de sangramento intracraniano.…”
unclassified